NUCLEOTIDES IN INFANT FEEDING - L.G. Mamonova (Вопросы современной педиатрии, 2007)
The article reviews the application of nucleotides-metabolites, playing a key role in many biological processes, for the infant feeding. The researcher provides the date on the nucleotides in the women's milk according to the lactation stages. She also analyzes the foreign experience in feeding newborns with nucleotides-containing milk formulas. The article gives a comparison of nucleotides in the adapted formulas represented in the domestic market of the given products.Key words: children, feeding, nucleotides.